Improving the psychological well-being of nurses through Islamic positive psychology training - Yuliatun, Ismiyati; Karyani, Usmi (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
Nurses have a heavy workload, which has become heavier during the COVID-19 pandemic, putting them at risk of psychological stress and affecting their psychological well-being, which impacts their mental health, work productivity, and self-development. In addition, their worship activities also decrease. However, there has been little research on Islamic-based interventions to improve the psychological well-being of nurses. This study seeks to determine the effectiveness of Islamic-based positive psychology training on improving such well-being by comparing the pre-test and post-test results of the control and experimental groups employed. The Ryff Psychological Well-being Scale and training were given to 38 respondents using consecutive sampling. The data were analyzed using SPSS 25.0, observation, independent assignments, and open questionnaires. The Mann-Whitney test results (Z = -2.416; p ˂ .05) and those of Wilcoxon (Z-experiment = -2.774; p ˂ .05 and Z-control = -0.081; p > .05) show that Islamic-based positive psychology training is effective in improving the psychological well-being of nurses. This research contributes to providing alternative interventions that can be used to foster positive activities and emotions that can improve such well-being.